1999
DOI: 10.1165/ajrcmb.20.6.3561
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Airway Hyperresponsiveness from Immunoglobulin E and Airway Eosinophilia in a Murine Model of Allergic Asthma

Abstract: Nonspecific airway hyperresponsiveness (AHR) is a hallmark of human asthma. Both airway eosinophilia and high serum levels of total and antigen-specific immunoglobulin E (IgE) are associated with AHR. It is unclear, however, whether either eosinophilia or increased IgE levels contribute directly to, or predict, the development of AHR. Investigations conducted with various murine models of asthma and different mouse strains have resulted in conflicting evidence about the roles that IgE and airway eosinophilia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
72
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 24 publications
8
72
0
1
Order By: Relevance
“…This is consistent with the reports of other investigators who have shown that IgE is not required for the development of eosinophilic airway inflammation and AHR in mice (21,(25)(26)(27). This could also be true in humans as observed by Haselden et al (28).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the reports of other investigators who have shown that IgE is not required for the development of eosinophilic airway inflammation and AHR in mice (21,(25)(26)(27). This could also be true in humans as observed by Haselden et al (28).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, many reports have also positively correlated eosinophils and/or IL-5 with AHR (18 -20). However, there have been negative reports as well, suggesting that eosinophils are neither required nor sufficient to induce AHR (21). In other reports, treatment with mAb to IL-5 had no effect on the reversal of established AHR in mice (22) and humans (23) despite complete suppression of eosinophil accumulation of airway tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Th2 responses are thought to be protective against parasite-mediated disease (60) but are associated with allergic disorders (59,61). It has been suggested that induction of Th2 cells or failure to mount a Th1 or regulatory T-cell response to foreign antigens in childhood may enhance atopic disease (10,49).…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a chronic disease of the respiratory tract and is tightly associated with airway hyperresponsiveness, increased mucus production, and infiltration of the bronchial mucosa by CD4 ϩ T cells (59). In allergic asthma there is evidence of an altered local T-cell response in favor of Th2 cytokines (interleukin-4 [IL-4], IL-5, and IL-13), which results in B-cell isotype switching to immunoglobulin E (IgE); mast cell, eosinophil, and basophil recruitment; and the production of a wide range of inflammatory mediators (61).…”
mentioning
confidence: 99%
“…11,12 However, the transfer of eosinophils to IL-5 À/À mice overcomes the intrinsic defect in T cell IL-13 production 13 and induces the development of AHR. 8 Thus, although the role of IL-5 in AHR is controversial, [6][7][8][9][14][15][16] the relationship between eosinophils and AHR is still correlative. 8,[11][12][13] Apoptosis is an important mechanism for the maintenance of homoeostasis in the immune system.…”
Section: Introductionmentioning
confidence: 99%